Perbedaan Pengaruh Latihan Gerak Terhadap Kekuatan Otot pada Pasien Stroke Non-Hemoragik Hemiparese Kanan Dibandingkan dengan Hemiparese Kiri - Irdawati Irdawati (MEDIA MEDIKA INDONESIANA, 2008)
The different effect of exercise on the muscle strength of patients with right and left non hemorrhagic hemipareses.Background: The stroke patients experienced difficulty in walking since they have disorder on their muscle strength, balance andmovement coordination, therefore they are difficult to do daily activities. Exercise make stroke patients improvement faster, because they will influence the movement sensation in the brain. The Objective of this study to prove the difference of movement exercise effect toward muscle strength on the right hemiparese of non-haemoragic stroke patients compared to those ones of the lefthemiparese.Method: An experimental research with two group designs; pretest and posttest groups. The research uses two groups of patients. The observed groups consist of 20 patiens for the group of stroke patients of the right hemiparese of non-haemoragic and 20 other patiens for the left hemiparese. They are given movement exercise according to physiotherapy program of Dr. Moewardi Hospital Surakarta. The data analysis was conducted using descriptive statistic and variable comparative hypothesis test which wereprocessed using SPSS version 13.0.Result: On the right and left hemiparese, an average increasing of muscle strength were 18.25 and 21.70 respectively. The result from Mann-Whitney test showed that there was no significant difference on the increasing value of muscle strength among the patient of right hemiparese (p=0.828). The average increasing of muscle strength as much as 57.10% on the right hemiparese and 71.92% on the left hemiparese.Conclusion: There was no significant difference on the increasing value of muscle strength among the patient of right and left hemiparese.Keyword : Movement Exercise, Stroke, Non-Hemoragik.ABSTRAKLatar Belakang: Penderita stroke mengalami kesulitan saat berjalan karena gangguan pada kekuatan otot, keseimbangan dan koordinasi gerak, sehingga kesulitan dalam melakukan aktivitas sehari-hari. Latihan gerak mempercepat penyembuhan pasien stroke, karena akan mempengaruhi sensasi gerak di otak. Tujuan penelitian ini untuk membuktikan perbedaan pengaruh latihan gerak terhadap kekuatan otot pada pasien stroke non-hemoragik hemiparese kanan dibandingkan dengan hemiparese kiri.Metode: Jenis penelitian ini adalah penelitian eksperimental dengan rancangan two group pretest dan posttest. Penelitian ini menggunakan dua kelompok pasien. Kelompok yang yang diteliti adalah pasien stroke non-hemoragik hemiparese kanan 20 pasien dan hemiparese kiri 20 pasien, yang diberi latihan gerak sesuai program fisioterapi Rumah Sakit Dr. Moewardi Surakarta. Analisis data dilakukan dengan statistik deskriptif dan uji hipotesis komparatif variabel dengan program SPSS versi 13.0.Hasil: Pada hemiparese kanan terjadi kenaikan rerata kekuatan otot sebesar 18,25 dan pada hemiparese kiri sebesar 21,70. Hasil uji statistik Mann-Whitney menyimpulkan tidak ada perbedaan yang bermakna pada kenaikan nilai kekuatan otot antara pasien hemiparese kanan dan hemiparese kiri (p=0,828). Rerata kenaikan nilai kekuatan otot 57,10% pada pasien stroke hemiparese kanan dan 71,92% pada pasien stroke hemiparese kiri.Simpulan: Tidak terdapat perbedaan kenaikan nilai kekuatan otot antara pasien stroke hemiparese kanan dibandingkan dengan hemiparese kiri setelah diberikan latihan gerak.